Neonatal Abdominal Hemangiomatosis: Propranolol beyond Infantile Hemangioma - Siu Ying Angel Nip; Kam Lun Hon; Wing Kwan Alex Leung; Alexander K. C. Leung; Paul C. L. Choi (Case Reports in Pediatrics)
Hemangioma is the most common vascular tumor of infancy; presentation is often as cutaneous infantile hemangioma (IH). Cutaneous hemangioma is a clinical diagnosis. Most IHs follow a benign course, with complete involution without treatment in the majority of cases. Visceral hemangioma often involves the liver and manifests as a life-threatening disorder. Hepatic hemangiomas may be associated with high output cardiac failure, coagulopathy, and hepatomegaly which generally develop between 1 and 16 weeks of age. Mortality has been reportedly high without treatment. We report a rare case of a male infant with neonatal hemangiomatosis with diffuse peritoneal involvement, which mimicked a malignant-looking tumor on imaging, and discuss therapeutic options and efficacy. Propranolol is efficacious for IH but generally not useful for other forms of vascular hemangiomas, tumors, and malformations. In our case of neonatal peritoneal hemangiomatosis, propranolol appears to have halted the growth and possibly expedite the involution of the hemangiomatosis without other treatments.